PENGEMBANGAN PANDUAN MELATIH BODY AWARENESS BERBASIS ANDROID UNTUK ANAK AUTIS - Khasanah, Al Um Aniswatun; Sholiha, Sangidatus; Vahlia, Ira (Media Penelitian dan Pengembangan Kesehatan, 2025)
Children with autism often face challenges in recognizing and controlling their own bodies, a condition referred to as body awareness. Deficits in body awareness can significantly affect motor skills, nonverbal communication, and social interaction. Despite the importance of this developmental domain, interactive training media tailored to the sensory and cognitive needs of children with autism remain limited. This study aims to develop an Android-based application to enhance body awareness in children with autism through the integration of music, video, and mirror game activities. The research utilized the ADDIE (Analysis, Design, Development, Implementation, Evaluation) development model. Instruments included expert validation questionnaires for both content and media, as well as user response surveys and comprehension tests administered to 30 children with autism in Metro City. Validation results indicated high feasibility, with ratings of 88.75% from media design experts and 90.00% from content experts. Effectiveness testing revealed a statistically significant improvement in body awareness, with a 20-point gain between pre-test and post-test scores (t = 13.70; p < 0.001; 95% CI: 16.70–23.30). These results suggest that the developed application is a practical, engaging, and effective tool for supporting body awareness development in children with autism, and it may serve as a valuable resource for educators, therapists, and parents.